SISTEM INFORMASI CUTI KARYAWAN BERBASIS WEB PADA PT GIKEN PRECISION INDONESIA - Sepentia, Nirpan; Harman, Rika (Computer Science and Industrial Engineering, 2023)
In the advancement of technology in the industrial era 4.0 is characterized by developments in all fields of activity, causing companies and government agencies to compete to keep up with changes by utilizing information technology For companies engaged in manufacturing, especially the PCBA (printed circuit board assemby) department at PT Giken Precision Indonesia is a manufacturing company located in the industrial area of citra buana park batu ampar. One of the needs of employees is a field that must be prioritized, Regarding matters of licensing and leave at a company is one of the company's obligations that must be given, most of the current leave information is still in paper format, one of the things that employees often complain about work is the submission of employee leave. Problems from this employee leave submission system such as the slow search for employee leave data, and the leave submission form is still filled in manually or in writing and there is no database so that data from leave is still stored in archive file cabinets and drawers so that leave information is still less efficient. The problem of applying for employee leave causes many parties to feel a lack of information such as how much data is left on their leave and the leave approval process must meet their respective superiors first, and data processing that is still written using paper format is a waste. Seeing the problems regarding leave.